The stupid ogre: oxford literacy web - Birkett, Georgie (Oxford University Press China, 1999)
Guides pupils through the core skills associated with learning to read and write with a range of literary styles. This work features stories, hilarious events, and illustrations. It aims to meet the requirements of the National Literacy Strategy, National Curriculum in England and Wales, and Common Curriculum in Northern Ireland.